Building Acoustic Analysis: Finite Element Method Model - Mohd Nasir, Mohd Naziman (Universiti Sains Malaysia, 2005)
The acoustics characteristic is important subjects that need to be considered in designing room or educational building. Malaysia is currently in the midst of the largest campaign of improving the quality of educational building. With the increased emphasis on education, engineers and architects must seize the opportunity to end a long-standing Malaysian practice, which is not concerning with the building of lecture room with inferior acoustics. This invisible problem has far reaching implications for learning process such as students must either struggle to hear or else become distracted or stop playing attention. The main reason for these situations is lack of awareness of the acoustic problem and its solutions. To overcome this problem, engineers and architects must begin the design process with educational building acoustics in mind. For this project, ANSYS 7.0 was used to model the enclosed area in 2-D which represent a building/room. Loads applied in form of frequencies at the top right hand corner of the model and the frequencies are 40 Hz, 50 Hz, 60 Hz, 70 Hz and 80 Hz. The results presented in form of tables and contour plots. From the results, area which has maximum/minimum pressure level can be determined.